2014
DOI: 10.1002/ptr.5269
|View full text |Cite
|
Sign up to set email alerts
|

Anti-allergic Effect of Intranasal Administration of Type-A Procyanidin Polyphenols Based Standardized Extract of Cinnamon Bark in Ovalbumin Sensitized BALB/c Mice

Abstract: The objective of the present work was to evaluate anti-allergic effects of intranasal administration of type-A procynidines polyphenols (TAPP) based standardized hydroalcoholic extract of Cinnamomum zeylanicum bark (TAPP-CZ) in ovalbumin (OVA)-induced experimental allergic rhinitis (AR) in BALB/c mice. Sixty male BALB/c mice were divided into six groups of ten each (G1-G6). The mice from G1 were nonsensitized and maintained as normal group. Remaining mice (G2-G6) were sensitized with OVA (500 μL solution, intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 43 publications
3
40
0
Order By: Relevance
“…63,64 It is considered that GSH act as cofactor for several protective enzymes that are important in defense mechanism of body from oxidative stress. 33,[65][66][67] There is association between the increase in blood pressure and the oxidative stress. Several clinical investigations showed that serum concentrations of MDA are high in the hypertensive patients than in normal individuals.…”
Section: Discussionmentioning
confidence: 99%
“…63,64 It is considered that GSH act as cofactor for several protective enzymes that are important in defense mechanism of body from oxidative stress. 33,[65][66][67] There is association between the increase in blood pressure and the oxidative stress. Several clinical investigations showed that serum concentrations of MDA are high in the hypertensive patients than in normal individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that activated phagocytic leukocytes have an ability to produce superoxide radicals that eventually leads to the production of reactive hydroxyl radical and peroxide (Adil et al, 2014[1]; Aswar et al, 2015[3]). Administration of TNBS may disrupt the endogenous antioxidant defense system leading to colonic oxidative damage (Li et al, 2011[47]).…”
Section: Discussionmentioning
confidence: 99%
“…Reactive Oxygen Species (ROS) played a vital role in the progression of various diseases [29][30][31][32][33][34] . However, natural compounds along with potential antioxidant property are topics of high current interest for the treatment of such disease of ROS originated and gastric ulcer being one of them.…”
Section: Discussionmentioning
confidence: 99%